Copper particle, conductive paste, and substrate

By developing copper particles with specific particle size distributions and production methods, the filling properties of copper particles in conductive pastes and substrates are significantly improved, addressing the inefficiencies in existing technologies and enhancing the performance of electronic components.

JP2025059351APending Publication Date: 2025-04-10FURUKAWA COMPANY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023169397
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing copper particles struggle with improved filling properties in conductive pastes and substrates, which affects the efficiency and reliability of electronic components.

Method used

Copper particles with specific particle size distributions, characterized by D 95/D 10 values of 4.20 or less and D 95 values ranging from 0.20 μm to 2.00 μm, are developed to enhance filling properties. These particles are produced through methods involving vibration drying and controlled moisture content, which optimize particle size and distribution.

Benefits of technology

The optimized copper particles demonstrate improved filling properties, leading to enhanced performance and reliability in conductive pastes and substrates, particularly in low-temperature simultaneous sintering ceramic substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059351000001
    Figure 2025059351000001
Patent Text Reader

Abstract

To provide: a copper particle with improved filling property; a conductive paste using the copper particle; and a substrate.SOLUTION: A copper particle has a value of 4.20 or less obtained by dividing D95 particle diameter (H2O) by D10 particle diameter (H2O), which is calculated by the following particle diameter measurement 1. [Particle diameter measurement 1] 0.1 g of the copper particle is mixed with 1 mL of 0.1 mass% dispersant aqueous solution. After radiating in-device ultrasonic for 5 min by using a laser diffraction / scattering-type particle diameter measurement device, a volume-based particle size distribution of the copper particle is measured to obtain each of values of D10 particle diameter (H2O), D50 particle diameter (H2O), and D95 particle diameter (H2O).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to copper particles, a conductive paste, and a substrate. [Background technology]

[0002] As a technique relating to copper particles, for example, the technique described in Patent Document 1 can be mentioned.

[0003] Patent Document 1 describes copper powder produced by a wet method, which has an absolute value of a zeta potential of 20 mV or more. It is described that the copper powder in Patent Document 1 can obtain easily crushable copper powder in which residual secondary particles are sufficiently reduced while reducing the burden of the crushing and classification processes from the dried cake. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-50947 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention provides copper particles having improved packing properties, and a conductive paste and a substrate using the same. [Means for solving the problem]

[0006] According to the present invention, there are provided copper particles, a conductive paste, and a substrate as described below.

[0007] [1] D, calculated by the particle size measurement 1 below 95 Particle diameter (H2O) is D 10 Copper particles having a particle size (H2O) of 4.20 or less. [Particle size measurement 1] 0.1 g of copper particles was mixed with 1 mL of a 0.1% by mass dispersant solution, and the mixture was irradiated with ultrasonic waves for 5 minutes using a laser diffraction / scattering particle size measuring device. The volume-based particle size distribution of the copper particles was then measured. 10 Particle size (H2O), D 50 Particle size (H2O), and D 95 Obtain the particle size (H2O) values, respectively. [2] Calculated by the particle size measurement 1, D 95 Particle diameter (H2O) is D 10 The copper particles according to [1], wherein the value obtained by dividing the particle diameter by the particle diameter (H2O) is 1.10 or more. [3] Calculated by the particle size measurement 1, D 95 Particle size (H2O) to D 10 The copper particles according to [1] or [2], wherein the particle diameter (H2O) minus the particle diameter is 0.05 μm or more and 1.50 μm or less. [4] D calculated by the particle size measurement 1 95 The copper particles according to any one of the above [1] to [3], having a particle diameter (H2O) of 0.20 μm or more and 2.00 μm or less. [5] D calculated by the particle size measurement 1 10 The copper particles according to any one of the above [1] to [4], having a particle diameter (H2O) of 0.05 μm or more and 0.50 μm or less. [6] D calculated by the particle size measurement 1 50 The copper particles according to any one of the above [1] to [5], having a particle diameter (H2O) of 0.10 μm or more and 1.00 μm or less. [7] D calculated by particle size measurement 2 below 50 The copper particles according to any one of the above [1] to [6], having a particle diameter (img) of 0.10 μm or more and 1.00 μm or less. [Particle size measurement 2] The images obtained by scanning electron microscope were analyzed to determine the 10 Particle size (img), D 50 Particle size (img) and D 90Obtain the particle size (img) value for each. [8] D calculated by the particle size measurement 1 50 Particle diameter (H2O) is calculated by the following particle diameter measurement 2 D 50 The copper particles according to any one of the above [1] to [7], wherein the value divided by the particle diameter (img) is 1.50 or less. [Particle size measurement 2] The images obtained by scanning electron microscope were analyzed to determine the 10 Particle size (img), D 50 Particle size (img) and D 90 Obtain the particle size (img) value for each. [9] The copper particles according to any one of [1] to [8] above, wherein the temperature at which the shrinkage rate of 1.0% calculated by the shrinkage rate measurement described below is 200° C. or higher. [Shrinkage rate measurement] 1 g of copper particles is weighed out and filled into a cylindrical mold having a diameter of 5 mm, and the copper particles are press-molded using a hydraulic press (discharge pressure of 10 MPa). The pellets obtained by press molding are crushed to obtain a granule sample. 0.67 g of the granule sample is weighed out and filled into a cylindrical mold having a diameter of 5 mm, and the granule sample is press-molded using a hydraulic press (discharge pressure of 10 MPa) to obtain a cylindrical pellet having a diameter of 5 mm and a height of 5 mm as a measurement sample. Using a thermomechanical analyzer, measurements are taken under the conditions of Ar flow rate: 200 mL / min, measurement load: 10 mN, measurement temperature range: 23 to 1000°C, and heating rate: 5°C / min, and the temperature at which the shrinkage rate becomes 1.0% is calculated.

[10] Tap density measured according to JIS Z2512:2012 is 2.5g / cm 3 The copper particles according to any one of the above [1] to [9].

[11] A conductive paste comprising the copper particles according to any one of [1] to

[10] above.

[12] A substrate comprising the conductive paste according to

[11] or a sintered body of the conductive paste.

[13] The substrate according to

[12] above, which is a low-temperature co-fired ceramic substrate. Effect of the Invention

[0008] According to the present invention, it is possible to provide copper particles with improved filling property, and a conductive paste and a substrate using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described. A numerical range "A to B" represents A or more and B or less, unless otherwise specified.

[0010] [Copper particles] Copper particles are used, for example, as a conductive paste. The conductive paste containing copper particles is also used, for example, as a wiring conductor of a substrate. When the conductive paste containing copper particles is used as a wiring conductor of a substrate, the conductive paste may be filled into a via hole of the substrate. Therefore, it is required to further improve the filling rate of copper particles in the via hole. The present invention provides copper particles having improved packing properties, and a conductive paste and a substrate using the same.

[0011] The copper particles of this embodiment, D 95 Particle diameter (H2O) is D 10 The value divided by the particle size (H2O) is 4.20 or less. The copper particles of this embodiment, D 95 Particle diameter (H2O) is D 10 From the viewpoint of further improving the filling property, the value divided by the particle size (H2O) is preferably 4.10 or less, more preferably 4.00 or less, even more preferably 3.90 or less, and even more preferably 3.80 or less, and the lower limit is not particularly limited, but may be, for example, 1.10 or more, 1.30 or more, 1.50 or more, or 1.80 or more.

[0012] According to the study by the present inventors, D 95 Particle diameter (H2O) is D 10It was found that the packing property of the copper particles is improved by adjusting the value divided by the particle diameter (H2O) to the above numerical range. 95 Particle diameter (H2O) is D 10 This is the first discovery that the measure of the value divided by the particle diameter (H2O) is effective as a design index for improving the packing of copper particles.

[0013] D 95 Particle diameter (H2O) is D 10 The value divided by the particle diameter (H2O) can be controlled, for example, by adjusting the conditions for drying the copper particles when producing the copper particles, more specifically, by drying the copper particles while vibrating them, adjusting the moisture content of the copper particles before drying, etc.

[0014] D of the copper particles of this embodiment 10 The particle size (H2O) is preferably 0.05 μm or more, more preferably 0.10 μm or more, even more preferably 0.15 μm or more, even more preferably 0.20 μm or more, even more preferably 0.25 μm or more, and is preferably 0.50 μm or less, more preferably 0.45 μm or less, even more preferably 0.40 μm or less.

[0015] D of the copper particles of this embodiment 50 The particle size (H2O) is preferably 0.10 μm or more, more preferably 0.20 μm or more, even more preferably 0.25 μm or more, even more preferably 0.30 μm or more, even more preferably 0.35 μm or more, even more preferably 0.40 μm or more, and is preferably 1.00 μm or less, more preferably 0.80 μm or less, even more preferably 0.70 μm or less, even more preferably 0.65 μm or less, even more preferably 0.60 μm or less.

[0016] D of the copper particles of this embodiment 95The particle size (H2O) is preferably 0.20 μm or more, more preferably 0.30 μm or more, even more preferably 0.40 μm or more, and even more preferably 0.50 μm or more. From the viewpoint of further improving the filling property, it is preferably 2.00 μm or less, more preferably 1.80 μm or less, even more preferably 1.60 μm or less, and even more preferably 1.50 μm or less.

[0017] The copper particles of this embodiment, D 95 Particle size (H2O) to D 10 From the viewpoint of further improving the filling property, the value obtained by subtracting the particle size (H2O) is preferably 1.50 μm or less, more preferably 1.40 μm or less, even more preferably 1.30 μm or less, even more preferably 1.20 μm or less, and even more preferably 1.10 μm or less, and the lower limit is not particularly limited, and may be, for example, 0.05 μm or more, 0.10 μm or more, 0.20 μm or more, or 0.25 μm or more.

[0018] Here, D 10 Particle size (H2O), D 50 Particle size (H2O), and D 95 The particle size (H2O) refers to the value calculated by Particle Size Measurement 1.

[0019] [Particle size measurement 1] 0.1 g of copper particles was mixed with 1 mL of a 0.1% by mass dispersant solution, and the mixture was irradiated with ultrasonic waves for 5 minutes using a laser diffraction / scattering particle size measuring device. The volume-based particle size distribution of the copper particles was then measured. 10 Particle size (H2O), D 50 Particle size (H2O), and D 95 Obtain the particle size (H2O) values, respectively. In particle size measurement 1, the dispersant refers to polyoxyethylene (20) sorbitan monolaurate.

[0020] D of the copper particles of this embodiment 10The particle size (img) is preferably 0.05 μm or more, more preferably 0.10 μm or more, and is preferably 0.50 μm or less, more preferably 0.40 μm or less.

[0021] D of the copper particles of this embodiment 50 The particle size (img) is preferably 0.10 μm or more, more preferably 0.20 μm or more, even more preferably 0.30 μm or more, and is preferably 1.00 μm or less, more preferably 0.80 μm or less, even more preferably 0.60 μm or less.

[0022] D of the copper particles of this embodiment 90 The particle size (img) is preferably 0.20 μm or more, more preferably 0.40 μm or more, even more preferably 0.50 μm or more, and preferably 2.00 μm or less, more preferably 1.80 μm or less, even more preferably 1.50 μm or less, even more preferably 1.20 μm or less.

[0023] Here, D 10 Particle size (img), D 50 Particle size (img), and D 90 The particle size (img) refers to the value calculated by particle size measurement 2.

[0024] [Particle size measurement 2] The images obtained by scanning electron microscope were analyzed to determine the 10 Particle size (img), D 50 Particle size (img) and D 90 Obtain the particle size (img) value for each. More specifically, D 10 Particle size (img), D 50 Particle size (img) and D 90 The particle size (img) refers to a value calculated by the method described in the Examples.

[0025] The copper particles of this embodiment, D 50 Particle diameter (H2O) is D 50From the viewpoint of further improving the filling property, the value divided by the particle size (img) is preferably 1.50 or less, more preferably 1.45 or less, even more preferably 1.40 or less, and even more preferably 1.35 or less, and the lower limit is not particularly limited, but may be, for example, 0.50 or more, 0.60 or more, or 0.70 or more.

[0026] The copper particles of the present embodiment may contain elements other than copper. Examples of the other elements include oxygen, carbon, nitrogen, chlorine, boron, etc. The content of the other elements is not particularly limited and may be an appropriate amount.

[0027] The temperature at which the copper particles of this embodiment have a shrinkage rate of 1.0% is preferably 200°C or higher, more preferably 300°C or higher, even more preferably 400°C or higher, even more preferably 500°C or higher, even more preferably 600°C or higher, even more preferably 650°C or higher, and even more preferably 700°C or higher, and the upper limit is not particularly limited, but may be, for example, 1000°C or lower, 950°C or lower, or 900°C or lower. It is preferable that the temperature at which the shrinkage rate becomes 1.0% is equal to or higher than the above lower limit, because when a conductive paste containing copper particles is used for a low-temperature co-fired ceramic substrate, the wiring conductor and the ceramic substrate can be co-fired more efficiently. Here, the temperature at which the shrinkage rate is 1.0% means a value calculated by the following shrinkage rate measurement.

[0028] [Shrinkage rate measurement] 1 g of copper particles is weighed out and filled into a cylindrical mold with a diameter of 5 mm, and the copper particles are press-molded using a hydraulic press (discharge pressure of 10 MPa). The pellets obtained by press molding are crushed to obtain a granule sample. 0.67 g of the granule sample is weighed out and filled into a cylindrical mold with a diameter of 5 mm, and the granule sample is press-molded using a hydraulic press (discharge pressure of 10 MPa) to obtain a cylindrical pellet with a diameter of 5 mm and a height of 5 mm as a measurement sample. Using a thermomechanical analyzer, measurements are taken under the conditions of Ar flow rate: 200 mL / min, measurement load: 10 mN, measurement temperature range: 23 to 1000°C, and heating rate: 5°C / min, and the temperature at which the shrinkage rate becomes 1.0% is calculated.

[0029] The copper particles of this embodiment preferably have a tap density of 2.5 g / cm as measured in accordance with JIS Z2512:2012. 3 More preferably, 2.8 g / cm 3 More preferably, 3.0 g / cm 3 More preferably, 3.2 g / cm 3 More preferably, 3.5 g / cm 3 The upper limit is not particularly limited, but is, for example, 5.0 g / cm 3 or less, 4.8 g / cm 3 or less, 4.5 g / cm 3 or less, 4.3 g / cm 3 It may be the following:

[0030] [Uses of copper particles] The copper particles of the present embodiment can be used, for example, in conductive pastes, paints, inks, etc., and can be preferably used in conductive pastes.

[0031] [Method of manufacturing copper particles] The method for producing the copper particles of this embodiment is not particularly limited, and examples thereof include a wet reduction method and a disproportionation method. Among these, the wet reduction method is preferred from the viewpoint of obtaining copper particles with a smaller particle size.

[0032] The method for producing copper particles of this embodiment preferably includes a step (A) of drying the hydrous copper particles while vibrating them, and more preferably includes the step (A), a step (B) of preparing a copper particle dispersion liquid (a), and a step (C) of performing solid-liquid separation of the copper particle dispersion liquid (a) to obtain the hydrous copper particles. Here, in this embodiment, the hydrous copper particles refer to a copper particle cake containing moisture, and refer to copper particles in a state after solid-liquid separation of the copper particle dispersion liquid (a) and before drying.

[0033] Below, each step of a preferred embodiment of the copper particle manufacturing method of this embodiment will be described.

[0034] <Step (A) of drying the hydrous copper particles while vibrating> The method for producing copper particles of this embodiment preferably includes a step (A) of drying the hydrous copper particles while vibrating them.

[0035] The moisture content of the hydrous copper particles, when the entire hydrous copper particles are taken as 100% by mass, is, from the viewpoint of adjusting the particle size of the copper particles within an appropriate range and further increasing the proportion of powdery copper particles in the obtained copper particles, preferably 30% by mass or less, more preferably 28% by mass or less, even more preferably 25% by mass or less, even more preferably 23% by mass or less, and even more preferably 20% by mass or less, and the lower limit is not particularly limited, but may be, for example, 5% by mass or more, 7% by mass or more, or 10% by mass or more. The moisture content of the hydrous copper particles means the moisture content of the hydrous copper particles before drying.

[0036] In step (A), the drying temperature is preferably 30°C or higher, more preferably 40°C or higher, even more preferably 45°C or higher, even more preferably 50°C or higher, and even more preferably 60°C or higher, from the viewpoint of further increasing the proportion of powdery copper particles in the obtained copper particles, and is preferably 100°C or lower, more preferably 95°C or lower, even more preferably 90°C or lower, and even more preferably 80°C or lower, from the viewpoint of further increasing the proportion of powdery copper particles in the obtained copper particles.

[0037] In step (A), from the viewpoint of further increasing the proportion of powdery copper particles in the obtained copper particles, the drying time is preferably 10 minutes or more, more preferably 30 minutes or more, even more preferably 60 minutes or more, even more preferably 80 minutes or more, even more preferably 120 minutes or more, and even more preferably 150 minutes or more, and from the viewpoint of further improving productivity, the drying time is preferably 24 hours or less, more preferably 12 hours or less, even more preferably 5 hours or less, and even more preferably 4 hours or less.

[0038] Step (A) may be carried out under reduced pressure or normal pressure, but is preferably carried out under reduced pressure.

[0039] In step (A), the method for drying the hydrous copper particles while vibrating them is not particularly limited, but it is preferable to dry the hydrous copper particles using a vibration dryer, and it is more preferable to dry the hydrous copper particles using a vertical vibration dryer. As the vertical vibration dryer, for example, a small vibration dryer VU-15 type (manufactured by Chuo Kakoki Co., Ltd.) can be used.

[0040] <Step (B) of Preparing Copper Particle Dispersion Liquid (a)> The method for producing copper particles of this embodiment preferably includes a step (B) of preparing a copper particle dispersion liquid (a).

[0041] The copper particle dispersion liquid (a) means a solution in which copper particles are dispersed in a solvent such as water. The solvent preferably contains water.

[0042] Step (B) preferably comprises a step (B-1) of dispersing a divalent copper compound in a solvent in the presence of a dispersant, and a step (B-2) of reducing the divalent copper compound to obtain a copper particle dispersion liquid (a).

[0043] The step (B-1) of dispersing a divalent copper compound in a solvent in the presence of a dispersant is carried out, for example, by adding a divalent copper compound to a solvent such as water, stirring the mixture, and then adding a dispersant.

[0044] The divalent copper compound includes, for example, at least one selected from the group consisting of copper sulfate, copper oxide, copper chloride, copper carbonate, copper nitrate, and the like, and preferably includes copper sulfate.

[0045] The dispersant is not particularly limited, but preferably includes at least one selected from the group consisting of gelatin, casein, sodium caseinate, ammonium caseinate, starch, dextrin, agar, sodium alginate, hydroxyethyl cellulose, carboxymethyl cellulose, methyl cellulose, ethyl cellulose, polyvinyl alcohol, polyvinylpyrrolidone, sodium polyacrylate, ammonium polyacrylate, stearic acid, polyethylene glycol, citric acid, aniline, and aniline derivatives, more preferably includes at least one selected from the group consisting of gelatin, casein, sodium caseinate, and ammonium caseinate, and even more preferably includes gelatin.

[0046] In step (B-1), the content of the dispersant, relative to 100 parts by mass of the copper compound, is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 1.0 parts by mass or more, and is preferably 3.0 parts by mass or less, more preferably 2.5 parts by mass or less, and even more preferably 2.0 parts by mass or less, from the viewpoint of further improving the dispersibility of the copper particles.

[0047] Step (B-2) of reducing a divalent copper compound to obtain a copper particle dispersion liquid (a) is carried out, for example, by adding a reducing agent to the dispersion liquid obtained in step (B-1) and reducing the divalent copper compound to obtain copper particles.

[0048] The reducing agent includes at least one selected from the group consisting of ascorbic acid; hydrazine-based reducing agents such as hydrazine, hydrazine hydrochloride, hydrazine sulfate, and hydrazine hydrate; sodium borohydride; sodium sulfite; sodium hydrogensulfite; sodium thiosulfate; sodium nitrite; sodium hyponitrite; phosphorous acid; sodium phosphite; hypophosphorous acid; sodium hypophosphite; aldehydes; alcohols; amines; and sugars.

[0049] The step (B-2) may be carried out under heating conditions in order to further promote the reduction of the divalent copper compound. The heating temperature is not particularly limited, but may be, for example, 10° C. or higher, 20° C. or higher, and 90° C. or lower, or 80° C. or lower.

[0050] In the step (B-2), the reduction step may be carried out only once, or may be carried out multiple times, but it is preferable to carry out the reduction step multiple times. That is, the step (B-2) preferably comprises a first reduction step and a second reduction step.

[0051] In the first reduction step, the reducing agent preferably comprises ascorbic acid. In the second reduction step, the reducing agent preferably comprises a hydrazine-based reducing agent, more preferably comprises hydrazine.

[0052] The method may further include a step of adjusting the pH of the dispersion between the first reduction step and the second reduction step. The step of adjusting the pH of the dispersion liquid is, for example, a step of adjusting the pH to 9.0 or more and 14.0 or less. The step of adjusting the pH of the dispersion liquid is carried out, for example, by adding a pH adjuster such as an aqueous sodium hydroxide solution to the dispersion liquid.

[0053] The copper particle dispersion liquid (a) may be free of the dispersant. The removal of the dispersant is carried out, for example, by adding a remover to the copper particle dispersion liquid (a). As the remover, for example, an aqueous solution of a hydroxide salt such as an aqueous solution of sodium hydroxide or an aqueous solution of potassium hydroxide; ion-exchanged water; or the like can be used.

[0054] The copper particles in the copper particle dispersion liquid (a) may be surface-treated. The surface treatment is carried out by treating the surfaces of the copper particles with a surface treatment agent such as a saturated fatty acid salt, e.g., sodium stearate; or an unsaturated fatty acid salt, e.g., sodium oleate.

[0055] <Step (C) of obtaining hydrous copper particles by performing solid-liquid separation of the copper particle dispersion liquid (a)> The method for producing copper particles of this embodiment preferably includes a step (C) of subjecting the copper particle dispersion liquid (a) to solid-liquid separation to obtain hydrous copper particles. Here, the copper particle dispersion liquid (a) in the step (C) includes a copper particle dispersion liquid (a) from which the dispersant has been removed, surface treatment has been performed, and the like.

[0056] The method for obtaining hydrous copper particles by performing solid-liquid separation of the copper particle dispersion liquid (a) is not particularly limited. For example, the hydrous copper particles can be obtained by at least one method selected from the group consisting of centrifugation, filtration, decantation, and the like. Among these, from the viewpoint of adjusting the moisture content of the hydrous copper particles to an appropriate range, it is preferable to obtain the hydrous copper particles by at least one method selected from centrifugation and filtration.

[0057] <Other processes> The method for producing copper particles of this embodiment may include other steps as appropriate. As the other steps, for example, a crushing step and the like can be mentioned.

[0058] [Conductive paste] The conductive paste of the present embodiment contains the copper particles of the present embodiment. The content of copper particles in the conductive paste of this embodiment, when the entire conductive paste is taken as 100 mass%, may be, for example, 1 mass% or more, 5 mass% or more, or 10 mass% or more, and may be 99 mass% or less, 97 mass% or less, or 94 mass% or less.

[0059] The conductive paste of the present embodiment may further contain a binder resin. The binder resin includes at least one selected from the group consisting of, for example, polyester resin, polyurethane resin, polyamide resin, polyvinyl chloride resin, polyacrylamide resin, polyether resin, acrylic resin, melamine resin, vinyl resin, phenol resin, epoxy resin, urea resin, vinyl acetate resin, polybutadiene resin, vinyl chloride-vinyl acetate copolymer resin, fluororesin, silicone resin, rosin, rosin ester, chlorinated polyolefin resin, modified chlorinated polyolefin resin, chlorinated polyurethane resin, cellulose-based resin, polyethylene glycol, polyethylene oxide, polypropylene oxide, polyvinyl alcohol, polyvinyl butyral, and polyvinylpyrrolidone.

[0060] The conductive paste of the present embodiment may further contain a solvent including at least one of water and an organic solvent. The organic solvent may be either a hydrophobic solvent or a hydrophilic solvent.

[0061] The hydrophobic solvent may be, for example, at least one selected from the group consisting of mineral oil, fatty acid, alcohol, and hydrocarbon.

[0062] Examples of the hydrophilic solvent include at least one selected from the group consisting of alkanediols such as ethylene glycol and propylene glycol; polyhydric alcohols such as glycerin; sugar alcohols; lower alcohols such as ethanol, methanol, propanol, and butanol; glycol ethers such as ethylene glycol monomethyl ether and ethylene glycol monoethyl ether; aliphatic amines such as methylamine and triethylamine; alkanolamines such as ethanolamine and triethanolamine; and amides such as N-methylacetamide and N-methylformamide.

[0063] The organic solvent may be used alone or in combination of two or more kinds.

[0064] The conductive paste of this embodiment can be applied to a substrate by, for example, an inkjet method or a screen printing method, dried, and then heated to form a conductive member such as a copper particle-containing wiring or thin film.

[0065] The conductive paste of the present embodiment can be produced by a known method, for example, by mixing the above-mentioned materials using a mixer such as a three-roll mill, a bead mill, a ball mill, a planetary mixer, or a disperser.

[0066] [substrate] The substrate of this embodiment includes the conductive paste of this embodiment or a sintered body of the conductive paste of this embodiment. The substrate of the present embodiment includes, for example, a coating of the conductive paste of the present embodiment or a sintered body of the conductive paste of the present embodiment in a predetermined region of a base material.

[0067] The substrate of this embodiment is, for example, a low-temperature co-fired ceramic substrate, a printed circuit board, a flexible substrate, or the like, and is preferably a low-temperature co-fired ceramic substrate.

[0068] The substrate of this embodiment is used, for example, as an electronic substrate for an automobile, a substrate for a high frequency module, a substrate for a semiconductor package, and the like.

[0069] The substrate of the present embodiment can be manufactured by a known method. For example, the conductive paste of the present embodiment can be screen-printed on a predetermined region of a base material (e.g., a green sheet, etc.), a plurality of base materials on which the conductive paste is printed are stacked to produce a laminate, and the laminate is fired to manufacture the substrate.

[0070] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. Furthermore, the present invention is not limited to the above-described embodiment, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention. EXAMPLES

[0071] The present embodiment will be described in detail below based on examples and comparative examples. Note that the present embodiment is not limited to the descriptions of these examples.

[0072] [Example 1] <Step (B-1) of dispersing a divalent copper compound in a solvent in the presence of a dispersant> First, 670 g of copper sulfate (manufactured by JX Metals Corporation) was added as a divalent copper compound to 2.26 L of ion-exchanged water, and the mixture was stirred using a stirrer (manufactured by HEIDON, product name: BL300). A dispersant solution prepared by the method described below was then added to obtain a dispersion. (Method of preparing a dispersant solution) As a dispersant, 10.7 g of gelatin (derived from cow bone, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., weight average molecular weight 100,000 to 300,000) was added to 0.5 L of ion-exchanged water, and the mixture was stirred with a magnetic stirrer (manufactured by IKA Corporation, product name: C-MAG HS4 digital) to prepare a dispersant solution.

[0073] <Step (B-2) of Obtaining Copper Particle Dispersion Liquid (a) by Reducing Divalent Copper Compound> A reducing agent solution prepared by the method described below was added to the dispersion. The dispersion was heated to 40°C and stirred for 3 minutes to reduce the copper compound, and a copper compound dispersion (b) was obtained. Next, a 24% by mass aqueous solution of sodium hydroxide was added to the copper compound dispersion (b) under the condition of a solution temperature of 40°C until the pH of the solution reached 10.6. At this time, the adjustment time until the pH of the solution reached 10.6 was 30 minutes. 400 g of hydrazine (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was added as a reducing agent to the copper compound dispersion (b) whose pH had been adjusted, and the solution was heated to 60°C and stirred for 60 minutes to reduce the copper compound, and a copper particle dispersion (a) was obtained. (Method of preparing reducing agent solution) As a reducing agent, 472 g of ascorbic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to 2.0 L of ion-exchanged water, and the mixture was stirred with a magnetic stirrer (manufactured by IKA Corporation, product name: C-MAG HS4 digital) to prepare a reducing agent solution.

[0074] <Step of Removing Dispersant> After stopping the stirring of the copper particle dispersion (a) and removing the supernatant, 5050 g of 1.2 mass% sodium hydroxide aqueous solution was added as a remover to remove the dispersant, and the mixture was stirred for 10 minutes. After stopping the stirring again and removing the supernatant, a reducing agent aqueous solution prepared by adding 27 g of hydrazine (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to ion-exchanged water was added to the copper particle dispersion (a), and the solution was heated to 50°C and stirred for 20 minutes. At this time, the pH of the copper particle dispersion (a) was 12.5.

[0075] <Surface treatment process> To the copper particle dispersion liquid (a) from which the dispersant had been removed, a surface treatment agent dispersion was prepared by adding 0.84 g of sodium stearate (manufactured by Kanto Chemical Co., Ltd.) to 0.5 L of ion-exchanged water as a surface treatment agent. The surface of the copper particles was then treated by adding the surface treatment agent dispersion to the copper particle dispersion liquid (a).

[0076] <Step (C) of obtaining hydrous copper particles by performing solid-liquid separation of the copper particle dispersion liquid (a)> The surface-treated copper particle dispersion (a) was subjected to solid-liquid separation using a centrifuge (manufactured by Kokusan Co., Ltd., product name: H-36) at a rotation speed of 3500 rpm for 5 minutes to obtain hydrous copper particles. The water content of the obtained hydrous copper particles was 13% by mass when the entire hydrous copper particles were taken as 100% by mass.

[0077] <Step (A) of drying the hydrous copper particles while vibrating> 817 g of the hydrous copper particles were dried while vibrating using a vertical vibration dryer under reduced pressure conditions at a drying temperature of 50° C. for a drying time of 180 minutes to obtain copper particles. The vertical vibration dryer used here was a small vibration dryer VU-15 (manufactured by Chuo Kakoki Co., Ltd.) with an adapter attached to the vacuum filter section and the body length of the dryer extended. The weight of the obtained copper particles was 708 g. The proportion of powdery copper particles in the obtained copper particles was 59 mass %, and the proportion of lump copper particles was 41 mass %. Here, the powdery copper particles refer to copper particles that are in powder form without being subjected to a crushing treatment in a mortar or the like. The lump copper particles refer to copper particles other than powdery copper particles. The present inventors believe that the powdery copper particles are obtained by crushing the lump copper particles by vibration drying.

[0078] [Example 3] Hydrated copper particles were obtained in the same manner as in Example 1. The moisture content of the obtained hydrous copper particles is shown in Table 1.

[0079] <Step (A) of drying the hydrous copper particles while vibrating> The hydrous copper particles were dried while vibrating in the same manner as in Example 1, except that the amount of hydrous copper particles charged, the drying temperature and the drying time were set to the conditions shown in Table 1, to obtain copper particles. The amount of copper particles obtained, the proportion of powdery copper particles in the obtained copper particles, and the proportion of lump copper particles are shown in Table 1.

[0080] [Examples 2 and 4] The copper particles were subjected to surface treatment in the same manner as in Example 1 to obtain a copper particle dispersion liquid (a).

[0081] <Step (C) of obtaining hydrous copper particles by performing solid-liquid separation of the copper particle dispersion liquid (a)> The surface-treated copper particle dispersion (a) was subjected to solid-liquid separation by suction filtration using qualitative filter paper (manufactured by ADVANTEC, product name: No. 131) to obtain hydrous copper particles. The moisture content of the obtained hydrous copper particles is shown in Table 1.

[0082] <Step (A) of drying the hydrous copper particles while vibrating> The hydrous copper particles were dried while vibrating in the same manner as in Example 1, except that the amount of hydrous copper particles charged, the drying temperature and the drying time were set to the conditions shown in Table 1, to obtain each copper particle. The amount of copper particles obtained, the proportion of powdery copper particles in the obtained copper particles, and the proportion of lump copper particles are shown in Table 1.

[0083] [Comparative Example 1] Except for not adding the reducing agent aqueous solution in the step of removing the dispersant, hydrous copper particles were obtained in the same manner as in Example 1. The moisture content of the obtained hydrous copper particles is shown in Table 1.

[0084] <Step of drying the hydrous copper particles> 150 g of the hydrous copper particles were dried under reduced pressure conditions at a drying temperature of 50° C. for a drying time of 720 min using a shelf dryer (manufactured by Yamato Scientific Co., Ltd., constant temperature shelf dryer DX602) to obtain copper particles. In Comparative Example 1, the copper particles were dried without vibration. The amount of the obtained copper particles was 108 g. The proportion of the lump copper particles was 100 mass %.

[0085] <Crushing process> The lump copper particles were crushed in a mortar to obtain powdered copper particles.

[0086] [Comparative Example 2] The copper particles were surface-treated in the same manner as in Example 1 to obtain a copper particle dispersion liquid (a).

[0087] <Step (C) of obtaining hydrous copper particles by performing solid-liquid separation of the copper particle dispersion liquid (a)> The surface-treated copper particle dispersion (a) was manually decanted to separate the solid and liquid, thereby obtaining hydrated copper particles. The moisture content of the obtained hydrated copper particles is shown in Table 1.

[0088] <Step (A) of drying the hydrous copper particles while vibrating> The hydrous copper particles were dried while vibrating in the same manner as in Example 1, except that the amount of hydrous copper particles, the drying temperature and the drying time were set to the conditions shown in Table 1, to obtain copper particles. The amount of copper particles obtained, the proportion of powdery copper particles in the obtained copper particles, and the proportion of lump copper particles are shown in Table 1.

[0089] [measurement] The following measurements were carried out in each of the Examples and Comparative Examples. Here, the copper particles obtained were in the form of powdered copper particles and lump-shaped copper particles, and various measurements were carried out on the powdered copper particles.

[0090] <Particle size (H2O)> 0.1 g of copper particles was mixed with 1 mL of a 0.1% by mass dispersant solution, and the mixture was irradiated with ultrasonic waves for 5 minutes using a laser diffraction / scattering particle size measuring device (manufactured by Horiba, Ltd., product name: LA-960V2). The volume-based particle size distribution of the copper particles was then measured. 10 Particle size (H2O), D 50 Particle size (H2O), and D 95 The particle size (H2O) values ​​were obtained respectively. Here, polyoxyethylene (20) sorbitan monolaurate was used as the dispersant.

[0091] <Particle size (img)> The copper particles were magnified and observed (10K magnification) using a scanning electron microscope to obtain images obtained by scanning electron microscopy (SEM images). The SEM images were analyzed using the image processing software ImageJ to obtain the following: 10 Particle size (img), D 50 Particle size (img) and D 90 The particle size (img) values ​​were obtained respectively. Specifically, the particle size was calculated according to the following procedure. 1. SEM images were imported into the image processing software ImageJ. 2. The scale of the SEM image was set as Known Distance using Set Scale. 3. The contrast threshold was adjusted using Threshold, and the image was binarized. 4. After binarization, particles were separated from the image using the Watershed method. 5. The particle size was calculated using the Analyze Particles function. The number of copper particles used to calculate the particle size was set to 200 or more. 6. From the obtained values, calculate the volume-based particle size distribution using the Area value, and D 10 Particle size (img), D 50 Particle size (img) and D 90 The particle size (img) values ​​were obtained respectively.

[0092] Based on the particle size values ​​obtained by the above measurement method, D 95 Particle diameter (H2O) is D 10 Divided by particle diameter (H2O), D 95 Particle size (H2O) to D 10 The value obtained by subtracting the particle size (H2O), and D 50 Particle diameter (H2O) is D 50 The values ​​were calculated by dividing the values ​​by the particle size (img).

[0093] <Temperature for shrinkage rate of 1.0%> 1 g of copper particles was weighed out and filled into a cylindrical mold having a diameter of 5 mm, and the copper particles were press-molded using a hydraulic press (discharge pressure of 10 MPa). The pellets obtained by press molding were crushed to obtain a granule sample. 0.67 g of the granule sample was weighed out and filled into a cylindrical mold having a diameter of 5 mm, and the granule sample was press-molded using a hydraulic press (discharge pressure of 10 MPa), to obtain a cylindrical pellet having a diameter of 5 mm and a height of 5 mm as a measurement sample. Using a thermomechanical analyzer (manufactured by NETZSCH, product name: TMA4000SA), measurements were performed under the conditions of Ar flow rate: 200 mL / min, measurement load: 10 mN, measurement temperature range: 23 to 1000°C, and heating rate: 5°C / min, and the temperature at which the shrinkage rate was 1.0% was calculated.

[0094] <Tap density> The tap density was measured in accordance with JIS Z2512:2012.

[0095] The results of each measurement are shown in Table 1. 95 Particle diameter (H2O) is D 10"Particle diameter (H2O) divided by" is "D 95 (H) / D 10 (H)," "D 95 Particle size (H2O) to D 10 The value obtained by subtracting the particle size (H2O) is "D 95 (H)-D 10 (H)" and "D 50 Particle diameter (H2O) is D 50 The value divided by the particle size (img) is "D 50 (H) / D 50 In Table 1, "-" means that the measurement was not performed.

[0096] [Table 1]

[0097] From Table 1, the tap density of the copper particles in the example is D 50 It can be seen that the tap density is improved compared to the copper particles of the comparative example, which has a similar particle diameter (img) value. In other words, it can be seen that the copper particles of this embodiment have improved packing properties.

Claims

1. D calculated by the following particle size measurement 1 95 Particle size (H 2 O) to D 10 Particle size (H 2 O) is 4.20 or less. [Particle size measurement 1] 0.1 g of copper particles was mixed with 1 mL of a 0.1% by mass aqueous dispersant solution, and the mixture was irradiated with ultrasonic waves for 5 minutes using a laser diffraction / scattering type particle size measuring device. The volume-based particle size distribution of the copper particles was then measured. 10 Particle size (H 2 O), D 50 Particle size (H 2 O), and D 95 Particle size (H 2 O) values ​​are obtained respectively.

2. D calculated by the particle size measurement 1 95 Particle size (H 2 O) to D 10 Particle size (H 2 2. The copper particles according to claim 1, wherein the value obtained by dividing the total mass of the copper particles by the mass of the copper particles is 1.10 or more.

3. D calculated by the particle size measurement 1 95 Particle size (H 2 O) to D 10 Particle size (H 2 3. The copper particles according to claim 1 or 2, wherein the value obtained by subtracting the particle diameter (μm) of the copper particle is 0.05 μm or more and 1.50 μm or less.

4. D calculated by the particle size measurement 1 95 Particle size (H 2 3. The copper particles according to claim 1 or 2, wherein the diameter of the particle is 0.20 μm or more and 2.00 μm or less.

5. D calculated by the particle size measurement 1 10 Particle size (H 2 3. The copper particles according to claim 1 or 2, wherein the diameter of the particle is 0.05 μm or more and 0.50 μm or less.

6. D calculated by the particle size measurement 1 50 Particle size (H 2 3. The copper particles according to claim 1 or 2, wherein the diameter of the particle is 0.10 μm or more and 1.00 μm or less.

7. D calculated by particle size measurement 2 below 50 The copper particles according to claim 1 or 2, having a particle diameter (img) of 0.10 μm or more and 1.00 μm or less. [Particle size measurement 2] The image obtained by the scanning electron microscope is analyzed to obtain D 10 Particle size (img), D 50 Particle size (img) and D 90 The particle size (img) values ​​are obtained for each.

8. D calculated by the particle size measurement 1 50 Particle size (H 2 O) is calculated by the following particle size measurement 2. 50 The copper particles according to claim 1 or 2, wherein the value divided by the particle diameter (img) is 1.50 or less. [Particle size measurement 2] The image obtained by the scanning electron microscope is analyzed to obtain D 10 Particle size (img), D 50 Particle size (img) and D 90 The particle size (img) values ​​are obtained for each.

9. 3. The copper particles according to claim 1 or 2, wherein the temperature at which the shrinkage rate of 1.0% calculated by the shrinkage rate measurement described below is 200°C or higher. [Shrinkage ratio measurement] 1 g of copper particles is weighed out, filled into a cylindrical mold having a diameter of 5 mm, and the copper particles are press-molded using a hydraulic press (discharge pressure of 10 MPa). The pellets obtained by press molding are crushed to obtain a granule sample. 0.67 g of the granule sample is weighed out, filled into a cylindrical mold having a diameter of 5 mm, and press-molded using a hydraulic press (discharge pressure of 10 MPa) to obtain a cylindrical pellet having a diameter of 5 mm and a height of 5 mm as a measurement sample. Using a thermomechanical analyzer, measurements are taken under the conditions of Ar flow rate: 200 mL / min, measurement load: 10 mN, measurement temperature range: 23 to 1000° C., and temperature rise rate: 5° C. / min, and the temperature at which the shrinkage rate reaches 1.0% is calculated.

10. The tap density measured in accordance with JIS Z2512:2012 is 2.5 g / cm 3 The copper particles according to claim 1 or 2.

11. A conductive paste comprising the copper particles according to claim 1 or 2.

12. A substrate comprising the conductive paste according to claim 11 or a sintered body of the conductive paste.

13. The substrate of claim 12 which is a low-temperature co-fired ceramic substrate.

Citation Information

Patent Citations

  • Easily crushable copper powder and method for producing the same

    JP2020050947A